2007
DOI: 10.1038/nbt1339
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and optimization of in vivo delivery of lipophilic siRNAs

Abstract: Cholesterol-conjugated siRNAs can silence gene expression in vivo. Here we synthesize a variety of lipophilic siRNAs and use them to elucidate the requirements for siRNA delivery in vivo. We show that conjugation to bile acids and long-chain fatty acids, in addition to cholesterol, mediates siRNA uptake into cells and gene silencing in vivo. Efficient and selective uptake of these siRNA conjugates depends on interactions with lipoprotein particles, lipoprotein receptors and transmembrane proteins. High-density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
795
0
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 867 publications
(842 citation statements)
references
References 25 publications
18
795
0
6
Order By: Relevance
“…The cholesterol moiety enhances retention of the conjugated siRNA in the circulation by binding to albumin, low-density lipoprotein and highdensity lipoprotein particles, as well as uptake in hepatocytes by binding to low-density lipoprotein receptors and uptake in the liver, gut, kidney and steroidogenic organs by binding to the scavenger receptor class B, type I receptors, which take up high-density lipoprotein. 40 Conjugation of cholesterol, as well as a-tocopherol, 41 lithocholic acid or lauric acid 42 to ApoB-siRNAs reduces serum cholesterol and ApoB mRNA levels in the liver after intravenous injection. Another example of this approach is 'siRNA dynamic polyconjugates' .…”
Section: Introductionmentioning
confidence: 99%
“…The cholesterol moiety enhances retention of the conjugated siRNA in the circulation by binding to albumin, low-density lipoprotein and highdensity lipoprotein particles, as well as uptake in hepatocytes by binding to low-density lipoprotein receptors and uptake in the liver, gut, kidney and steroidogenic organs by binding to the scavenger receptor class B, type I receptors, which take up high-density lipoprotein. 40 Conjugation of cholesterol, as well as a-tocopherol, 41 lithocholic acid or lauric acid 42 to ApoB-siRNAs reduces serum cholesterol and ApoB mRNA levels in the liver after intravenous injection. Another example of this approach is 'siRNA dynamic polyconjugates' .…”
Section: Introductionmentioning
confidence: 99%
“…The most typical derivatization is with long-chain fatty acids, whereas derivatization with cholesterol has been little explored (57). However, a recent report on the comparative efficacy in vivo of intravenously administered lipophilic derivatives of siRNA showed that derivatization with cholesterol and related molecules gave the highest biological activity (58). Therefore, we investigated whether derivatization with cholesterol, in addition to providing improved antiviral potency, also extends the half-life of the peptide in vivo.…”
Section: Effect Of Lipid Derivatization On the Pharmacokinetics Of C3mentioning
confidence: 99%
“…Wolfrum et al [111] demonstrated that cholesterol-conjugated siRNA is taken up in murine models by a lipoprotein-dependent mechanism. Delivery of the siRNA conjugates depended upon interactions with lipoprotein particles, lipoprotein receptors and transmembrane proteins.…”
Section: "Ad" System -Based Deliverymentioning
confidence: 99%